An Innovative Cryptography Safety Algorithm Called S-RSB-23 for Protecting Data Using Machine Learning Algorithm - Basha, C. Bagath; Rajaprakash, S.; Aggarwal, Nitisha; Riyazuddin, MD; Sirajuddin, Mohd; Gole, Srihari Babu (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The modern world is dependent on information as a result of the fact that information is most compelling when presented in an open setting. The only judgements that could be made with this data concerned people’s lives and the global financial market and were either good or negative. We need to be able to store, analyse, and organise the ever-increasing quantity of data that we are collecting on a daily basis since it will only continue to rise. These Twitter data will be analysed using Machine Learning Algorithms (MLA), which will also download them for further study. This data analysis does not provide dependable cryptographic techniques. In this study, we present the quick encryption technique S-RSB-23 and show how to transform the ASCII code to the corresponding hexadecimal value using this approach. The cells in this transformed code have been paired and then swapped. In comparison to the SALSA technique, the S-RSB-23 approach offers a much improved level of encryption throughput.